2021
DOI: 10.33314/jnhrc.v18i4.2566
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Pattern of Gram-Negative Bacteria Causing Lower Respiratory Tract Infections in Kathmandu University Hospital

Abstract: Background: Respiratory tract infection due to Gram-negative bacteria is a common cause of morbidity and mortality worldwide. This study was carried out to determine the antimicrobial susceptibility pattern of Gram-negative bacteria from patients with lower respiratory tract infection visiting Kathmandu University Hospital.Methods: A total of 3,403 respiratory samples including sputum and endotracheal aspirates were processed and antibiotic resistance pattern was determined following Clinical Laboratory Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…This is contrary to a study conducted in Kenya that reported 95.4% growth of bacterial pathogens [ 19 ]. Previous studies carried out in Nepal reported no bacterial growth in 56.4% and 49.6% of the samples [ 20 , 21 ]. The varying results in this study could be due to other etiological agents of respiratory infections which include viruses and fungi.…”
Section: Discussionmentioning
confidence: 83%
“…This is contrary to a study conducted in Kenya that reported 95.4% growth of bacterial pathogens [ 19 ]. Previous studies carried out in Nepal reported no bacterial growth in 56.4% and 49.6% of the samples [ 20 , 21 ]. The varying results in this study could be due to other etiological agents of respiratory infections which include viruses and fungi.…”
Section: Discussionmentioning
confidence: 83%
“…Also, this might be caused by the lengthy usage of antibiotics in the elderly patients who are vulnerable to respiratory tract infections. 25 The drug resistance rates against ceftriaxone and sulbactam/ampicillin were lower in neonatal group than in non-neonatal group, compared with infants and children, possibly because of less chance of exposure to broad-spectrum antibiotics. 26 In contrast, a previous multicentre study revealed a higher ESBL-positive percentage in children than in the old patients.…”
Section: Discussionmentioning
confidence: 90%
“…Antibiotic resistance rates of sputum isolates were higher in older patients than in younger patients, partly due to the higher prevalence of ESBL-positive strains in the older patients. Also, this might be caused by the lengthy usage of antibiotics in the elderly patients who are vulnerable to respiratory tract infections 25. The drug resistance rates against ceftriaxone and sulbactam/ampicillin were lower in neonatal group than in non-neonatal group, compared with infants and children, possibly because of less chance of exposure to broad-spectrum antibiotics 26.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that coronary heart disease, diabetes, shock, renal insufficiency and deep venous catheterization are the main risk factors for death from carbapenem-resistant Gram-negative bacteria pneumonia (24)(25). Some scholars have pointed out in the study that patients with coronary heart disease often suffer from cardiac insufficiency under the blow of refractory infection, resulting in death (26)(27); Diabetic patients with vascular diseases of other organs, severe acute complications of diabetes will increase the mortality of patients. It is necessary to strengthen the monitoring of diabetic patients to prevent complications (28)(29).…”
Section: Discussionmentioning
confidence: 99%